O nowej koncepcji okoliczności powołania biskupa Jordana - Sikorski, Dariusz Andrzej (Ecclesia. Studia z Dziejów Wielkopolski, 2014)
The article provides a systematic analysis of a body of conceptions on the beginnings of the bishopric in Poznań presented by Tomasz Jasiński in several of his lesser studies. In the light of the performed analysis it must be concluded that the basic points of Jasiński's conception, such as the criticism of Thietmar's account of the beginnings of the Magdeburg metropolis, the circumstances of the creation of Jordan's episcopal see on the occasion of the Roman imperial coronation and the legal status of Jordan's episcopacy are either contestable or simply unsupportable. Consequently, the entire claim should be rejected.